Accuracy, user-friendliness and usefulness of the Cobas h232 point-of-care test for NT-proBNP in primary care. Issue 6 (20th December 2017) - Hex, Chiel; Smeets, Miek; Penders, Joris; Van Hoof, Viviane; Verbakel, Jan; Buntinx, Frank; Vaes, Bert
Abstract : Aims: N-terminal pro-B-type natriuretic peptide (NT-proBNP) has been shown to be useful for ruling out heart failure in primary care. In this study, we examined the accuracy of the Cobas h232 point-of-care (POC) instrument in primary care compared with an in-hospital measurement. Furthermore, we investigated the user-friendliness and usefulness of the POC device. Methods: Five general practitioner (GP) groups were asked to evaluate adult patients who were suspected of having heart failure and to test NT-proBNP with the Cobas h232. The samples were subsequently delivered to and analysed at a central hospital laboratory by the Cobas e602 using conventional transport and storage. Difference between the paired measurements was analysed using a percentage difference plot, and correlation was assessed using Passing-Bablok linear regression analysis. User-friendliness and usefulness were assessed using semistructured questionnaires. Results: Nineteen GPs studied 94 patients. Passing-Bablok analysis showed a slope of 1.05 (95% CI 1.00 to 1.11) (R 2 =0.97). The percentage difference plot showed a mean difference of 15.7% (95% CI −46.0% to –77.4%). User-friendliness and usefulness had median scores of 4 or 5 on a five-point Likert scale. Eighteen out of 19 GPs confirmed that the device influenced their clinical practice. During the study, GPs' confidence in using NT-proBNP increased significantly from a mean score of 4.4 (95% CI 3.2 to 5.6) to 7.6 out of 10 (95% CI 7.1 to 8.2). Conclusions: The Cobas h232 NT-proBNP POC test proved to be an accurate, user-friendly and useful test in primary care. Nearly all participating GPs were convinced that the test could benefit clinical decision making.